Teacher's Perspective on the Implementation of the Law on Teachers and Lecturers in Realizing Excellent Teacher Resources in Medan City - Ida Martinelli; Nalil Khairiah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The Law on Teachers and Lecturers is a government policy in improving the quality of teachers, namely by providing certification as an acknowledgment of teachers as professionals, accompanied by certification allowances that can be used by teachers to improve their quality or competence. With the implementation of the Law on Teachers and Lecturers, the government targets the realization of superior teacher resources in the sense of being able to meet all the requirements set out in the law. As the party who is given the obligation to have educator certification, it is necessary to know how the teacher's perspective on the implementation of the Law on Teachers and Lecturers in realizing superior teacher resources in the city of Medan, as an effort to measure the successes and weaknesses in the implementation of the Law on Teachers and Lecturers . This research was conducted using a qualitative descriptive research method. The selected resource persons came from teachers from various levels of education units and school supervisors as parties directly involved in the implementation of the Law on Teachers and Lecturers. The results of the study indicate that the teacher's perspective on the implementation of the Law on Teachers and Lecturers has been going well and has an impact on increasing teacher competence and motivation in carrying out their duties, but there are several weaknesses such as: there are still teachers who do not understand the Law on Teachers and Lecturers, find it difficult in teacher certification procedures, do not meet the required qualifications, weak teacher administration, limited certification quotas, remote PPLG implementation sites.